UTILIZATION OF THERMAL ENERGY THROUGH CONVERSION VIA THERMOELECTRIC MATERIAL AND STORAGE VIA PHASE CHANGE MATERIAL FOR ENERGY CONSUMPTION EFFICIENCY OF BUILDING - Rifqi Muchtar, Ahmad
Thermoelectric material is developed for utilizing waste heat energy to be converted into electrical energy. These development efforts include on finding the right material composition to obtain optimal thermal and electrical properties in achieving the best thermoelectric performance. The most referred thermoelectric material performance is Figure of Merit and Power Factor. Tin Telluride (SnTe) is a material similar to Lead Telluride (PbTe) with the main advantages of being environmentally friendly and non-toxic. Intrinsic properties of SnTe in the form of a large number of charge carriers and small band gap cause its low thermoelectric performance. Various studies have been carried to improve the thermoelectric performance of SnTe, including doping. Transition metals such as Vanadium, Zinc, and Manganese have shown their potential as SnTe doping to improve thermoelectric performance. The synthesis of SnTe doped with Titanium and Zirconium transition metal elements, shows that all samples have a single phase with fcc cubic crystal structure. Thermal characterization shows that doping causes a decrease in thermal conductivity. Electrical characterization shows that doping causes a decrease in electrical conductivity and increase in the Seebeck coefficient. In this study, two compositions of materials with the best performance were obtained, namely Sn?.??Zr?.??Te with zT 0.58 and SnTi?.??Te with zT 0.52. In the next step, two codoped compositions Sn0.88Ti0.03Mn0.09Te, dan Sn0.89Zr0.02Mn0.09Te have been synthesized. The characterization result shows that the power factor increase in low temperature range but stagnant in higher temperature range. However, the codoping process improve the thermoelectric performance by the increase of zTmax to 0.72 for Ti-Mn-doped and to 0.70 for Zr-Mn-doped. The development of shape stabilized phase change materials (SSPCM) for thermal comfort applications in buildings is faced with the challenges of the low thermal conductivity of PCM, the use of environmentally friendly materials, anti-leakage, and economic feasibility. The use of activated carbon as supporting structure have been proven in various researchs to increase thermal conductivity of PCM. The use of abundantly available renewable materials, as well as the simple synthesis method, can answer some of these problems. For the first time the use of food grade coconut oil and coconut shell based activated carbon as precursors for the synthesis of bio shape stabilized phase change materials (bioSSPCM) was reported. Despite its low melting enthalpy, the simple physical blending by heating and mixing is very reliable as it gives thermally stable SSPCM and anti-leakage properties on top of its economical advantage. There is no distinct difference between food grade and analytical grade coconut oil, in terms of its application for SSPCM materials. For comparison purposes, octadecane and charcoal based activated carbon were used. The mixing of octadecane into activated carbon with the simple physical blending synthesis results in some leakage which is suspected caused by the low viscosity of octadecane. Besides, the existence of submacro and macroporous in activated carbon potentially cause the leakage because of the low capillary force. The simulation of the integration of the SSPCM material into building envelope were carried out using EnergyPlus 9.6 software. From the simulation results, in general, it was observed that the addition of SSPCM shows the potential for decreasing room temperature and decreasing electricity consumption if the room uses air conditioning. The comparison with insulator, in Jakarta weather, the use of insulators shows the best results, however, in terms of thickness increment, SSPCM shows the most significant effect. In Bandung weather, the use of PCM and SSPCM shows a more significant effect when compared to Jakarta weather. The variation of SSPCM position in building shows that integration of SSPCM into external layer of the wall shows the most significant effect compared to two other positions (plafon and as internal mass). The addition of natural ventilation also shows 2-3 oC decreement of inside temprature. So far, the SSPCM melting temperature shift test has not shown positive results regarding a decrease in inside temperature or energy consumption.